PENGARUH PENERAPAN MODEL DISCOVERY TERHADAP KETERAMPILAN PROSES SAINS SISWA DI SEKOLAH DASAR - Kastiarahmi, Leni; Kresnadi, Hery; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to know the effect of discovery model on thescience process skills in learning student fifth grade Elementary School in Pontianak. The experimental reseach method was used in this research. The form of the experimental research used was one group pretest postest design. Sample in this research weer students fourth grade which consisted of 24. Instrument gatherer data of student learning the test results obtained using measurement technique. Instrument gatherer data of student learning the test results obtained from pre-test and post-test. The result of data analysis showed that mean score of student?s post-test was 72,50Based on t-test analysis, thitung of (8,81) and ttabel (1,714). Which means, thitung (8,81) >ttabel (1,714), then Ha accepted. The result of effect size was 0,68 which mean medium criteria on ES<0,7. So, it can be concluded there was a significant effect of using discovery model on the science process skills in learning student fifth grade Elementary School in Pontianak Keywords:Effect, Discovery model, Science process skill.